PENGETAHUAN MAHASISWA TATA BUSANA TENTANG ZERO WASTE PATTERN - Suci Rahmawati; Puji Hujria Suci (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Textile waste is one of the 2nd largest types of waste in the world. The increasing amount of textile waste will have an impact on the environment. There has not been much development of clothing with Zero Waste techniques in Indonesia, and students as social beings also play an important role in environmental renewal through waste reduction. The purpose of the research is to understand the level of cognitive knowledge of fashion students about Zero Waste Pattern based on indicators of 6 levels of knowledge (C1-C6) namely knowledge, understanding, application, analysis, synthesis and evaluation. The method used in this research is descriptive quantitative with one variable, which is knowledge about Zero Waste Pattern. The research sample was 77 respondents who were active students of the Family Welfare Education Study Program, Padang State University, class of 2019-2022. Data collection uses Google forms with tests in the form of true and false questions or gutman scales that have proven their validity and reliability. The impact of research on fashion students' knowledge of Zero Waste Pattern there are 6 levels of knowledge to be indicators in this study with the percentage of indicators of Knowledge (C1) 57%, Understanding (C2) 62%, Application (C3) 64%, Analysis (C4) 54%, Synthesis (C5) 66% and Evaluation (C6) 76% of Zero Waste Pattern with part of the indicator remembering the terms in Zero Waste Pattern, explaining the understanding of the concept of Zero Waste Pattern, explaining the stages of Zero Waste Pattern, applying the Zero Waste Pattern method, summarizing the material from the Zero Waste Pattern technique, combining concepts about the Zero Waste Pattern approach, assessing designs, concepts and assessing public awareness in the Zero Waste Pattern technique. The research obtained the highest percentage of 80%, followed by a moderate level of knowledge of 15% and a low level of knowledge of 3%. It can be concluded that 62 Fashion Management students have knowledge about Zero Waste Pattern. Suggestions that can be given after this research is obtained so that students can realize the work of services or products in the field of fashion related to the concept of Zero Waste Pattern.Keywords: Knowledge, Fashion, Zero Waste PatternAbstrakLimbah tekstil salah satu jenis limbah terbesar ke-2 di dunia. Meningkatnya jumlah limbah tekstil akan berdampak pada lingkungan. Belum banyak pengembangan pakaian dengan teknik Zero Waste di Indonesia, dan mahasiswa sebagai makhluk sosial juga berperan penting dalam pembaruan lingkungan lewat pengurangan limbah. Tujuan dilaksanakan penelitian adalah untuk memahami tingkat pengetahuan kognitif mahasiswa tata busana mengenai Zero Waste Pattern berdasarkan indikator 6 tingkatan pengetahuan (C1-C6) yaitu pengetahuan, pemahaman, penerapan, analisis, sintesis dan evaluasi. Cara yang dipakai pada penelitian ini adalah deskriptif kuantitatif dengan satu variable, ialah pengetahuan tentang Zero Waste Pattern. Sampel penelitian adalah 77 orang responden yang adalah mahasiswa aktif Tata Busana Prodi Pendidikan Kesejahteraan Keluarga, Universitas Negeri Padang, angkatan 2019-2022. Pengumpulan data memakai Google form dengan tes berupa soal benar salah atau skala gutman yang telah terbukti validitas dan reliabilitasnya. Dampak penelitian pada pengetahuan mahasiswa tata busana tentang Zero Waste Pattern ada 6 tingkatan pengetahuan menjadi indikator pada penelitian ini dengan persentase indikator Pengetahuan (C1) 57%, Pemahaman (C2) 62%, Penerapan (C3) 64%, Analisis (C4) 54%, Sintesis (C5) 66% dan Evaluasi (C6) 76% terhadap Zero Waste Pattern dengan bagian indikator mengingat istilah dalam Zero Waste Pattern, menjelaskan pemahaman tentang konsep Zero Waste Pattern, menjelaskan tahapan Zero Waste Pattern, menerapkan metode Zero Waste Pattern, menyimpulkan materi dari Teknik Zero Waste Pattern, menggabungkan konsep-konsep tentang pendekatan Zero Waste Pattern, menilai desain, konsep dan menilai kesadaran masyarakat dalam teknik Zero Waste Pattern. Penelitian memperoleh persentase tertinggi yaitu 80%, selanjutnya tingkat pengetahuan sedang 15% dan tingkat pengetahuan rendah 3%. Dapat disimpulkan bahwa 62 mahasiswa Tata Busana memiliki pengetahuan tentang Zero Waste Pattern. Saran yang dapat diberikan setelah penelitian ini didapatkan agar mahasiswa dapat untuk mewujudkan karya jasa atau produk bidang busana yang berkaitan dengan konsep Zero Waste Pattern.Kata Kunci: Pengetahuan, Tata Busana, Zero Waste PatternAuthors:Suci Rahmawati : Universitas Negeri PadangPuji Hujria Suci : Universitas Negeri PadangReferences ANITA KURNIAWATI. (2021). PENGETAHUAN MAHASISWA TATA BUSANA TENTANG ZERO WASTE FASHION.Arikunto, S. (2010). Prosedur penelitian: Suatu pendekatan praktik.Arikunto, S. (2013). Prosedur penelitian: Suatu pendekatan praktik.Fisher, E. (2015). Recycled & reclaimed fibers:less waste, less energy.Kementerian, P. P. N., BAPPENAS, P. K. D., & UNDP, I. (2021). Manfaat Ekonomi, Sosial, dan Lingkungan dari Ekonomi Sirkular di Indonesia. Ringkasan Bagi Pembuat Kebijakan.Muttaqien, T. Z., & Adiluhung, H. (2021). USAHA KECIL MENENGAH DI BANDUNG MENDUKUNG SUSTAINABLE DESIGN MELALUI PEMBUATAN FURNITUR BERBAHAN LIMBAH KAYU MENGGUNAKAN KONSEP NIRMANA DWIMATRA. Gorga¯: Jurnal Seni Rupa, 10(1), 01. https://doi.org/10.24114/gr.v10i1.20731Novrita, S. Z. (2007). Peningkatan Motivasi Belajar Melalui Media Pembelajaran Pada Mata Kuliah Busana Pria (Action Research) Di Jurusan Kesejahteraan Keluarga FT UNP.Putri, A. W. A., & Kristi, J. I. (2020). EKSPLORASI ECO PRINTING DAUN LANANG DAN PEWARNAAN ALAM KAYU TEGERAN PADA KAIN RAYON SEBAGAI POTENSI MATERIAL FASHION SUSTAINABLE. Gorga¯: Jurnal Seni Rupa, 9(2), 317. https://doi.org/10.24114/gr.v9i2.20271Rissanen, T., & McQuillan, H. (2023). Zero waste fashion design. Bloomsbury Publishing.Siswoyo, D., Sulistyono, T., & Dardiri, A. (2007). Ilmu pendidikan. Yogyakarta: UNY press.Suardi, M. (2015). Belajar dan pembelajaran. Deepublish.Suci, P. H., Puspaneli, P., & Yupelmi, M. (2023). Tutorial Video Development of 3D Women™s Fashion Design Using CLO3D for Clothing Production Design Courses. Proceedings of Vocational Engineering International Conference, 5, 737“740.Suyedi, S. S., & Idrus, Y. (2019). HAMBATAN-HAMBATAN BELAJAR YANG MEMPENGARUHI HASIL BELAJAR MAHASISWA DALAM PEMBELAJARAN MATA KULIAH DASAR DESAIN JURUSAN IKK FPP UNP. Gorga¯: Jurnal Seni Rupa, 8(1), 120. https://doi.org/10.24114/gr.v8i1.12878Widagdo, A., Pramumijoyo, S., & Harijoko, A. (2018). Tectonostratigraphy-volcanic of Gajah-Ijo-Menoreh Tertiary volcanic formations in Kulon Progo mountain area, Yogyakarta-Indonesia. IOP Conference Series: Earth and Environmental Science, 212, 012052. https://doi.org/10.1088/1755-1315/212/1/012052Zahra, A. (2020). Apa Itu Fesyen Berkelanjutan (Sustainable Fashion).